2021
DOI: 10.3390/w13091260
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Removal from Electroplating Wastewater by Waste Fiber-Based Poly(amidoxime) Ligand

Abstract: An efficient and economical treatment technology for heavy metal removal from the electroplating wastewaters is needed for the water purification. Therefore, pure cellulosic materials were derived from two waste fiber (pandanus fruit and durian rind) and conversion of the cellulose into the poly(acrylonitrile)-grafted material was accomplished by free radical grafting system. Thereafter, poly(amidoxime) ligand was produced from the grafted materials. Sorption capacity (qe) of several toxic metals ions was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Several work reported that wastewater from some plating and semiconductor industry contains metal in the range below 100 ppm to a few hundred ppm [ 22 , 23 , 24 , 25 , 26 , 27 ]. Synthetically prepared aqueous feed that contained mixture of 100 ppm of each chromium (VI), copper and zinc, which are commonly found in these industrial wastewater, were used in this study to represent the wastewater that is generated from those industries.…”
Section: Methodsmentioning
confidence: 99%
“…Several work reported that wastewater from some plating and semiconductor industry contains metal in the range below 100 ppm to a few hundred ppm [ 22 , 23 , 24 , 25 , 26 , 27 ]. Synthetically prepared aqueous feed that contained mixture of 100 ppm of each chromium (VI), copper and zinc, which are commonly found in these industrial wastewater, were used in this study to represent the wastewater that is generated from those industries.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we used waste fibers such as pandanus fruit fiber and durian rind to obtain a lower cost adsorbent. 44 Pure cellulose materials were extracted from both waste fibers. The low-cost cellulose was converted into PA ligands, and they were characterized by FT-IR.…”
Section: Sorption and Removal Of Metal Ions By Pa Resinsmentioning
confidence: 99%
“…44 It has been observed that most metals show lower adsorption capacity in higher acidic conditions due to the protonation of amino groups in amidoxime ligands. 44 Definitely, the amidoxime chelating group (C(NH 2 )N OH) exhibited an amphoteric nature. 35 At lower pH (<7), the basic amino group (−NH 2 ) tends to prevent protonation, which turns into NH 3 + , and simultaneously, the reduction of ionization of the acidic hydroxyl group (−OH) is likely to occur.…”
Section: Effect Of Ph For Adsorption Of Metalmentioning
confidence: 99%
“…Surface functional groups such as amino and hydroxyl groups that mostly exist on polymers, have a strong affinity for heavy metal ions [24]. Therefore, Table 10 represents various polymer-based adsorbents with all related heavy metal adsorption capacities, with the optimum pH, preferred kinetic and isotherm model [52][53][54][55][56][57].…”
Section: Polymeric Adsorbentmentioning
confidence: 99%